SPEECH FUNCTION AND MOOD IN THE 2014 INDONESIAN PRESIDENTIAL CANDIDATESDEBATE - JuniArta Sari Tambunan; Amrin Saragih (State University of Medan, 2015)
This study deals with Speech Function and Mood used in the 2014 IndonesianPresidential Candidates Debate. This study was conducted by using descriptivequalitative method. The purpose of this study is to find out the types of SpeechFunction and Mood used in the debate based on Halliday’s theory. The data ofthis study were the utterances of both President Candidates, namely Jokowi Dodoand PrabowoSubianto. The findings show that both President candidates used alltypes of Speech Function in the debate, which Statement are 464 utterances(82.71%), Question are 51 utterances (9.09%), Command are 34 utterances(6.06%) and Offer are 12 utterances (2.14%). It is also found that they usecongruent and metaphorical realization of Mood in debating. The use ofCongruent Mood of declarative are 469 utterances (83.6%), Interrogative are 49utterances (8.73%), and Imperative are 33 utterances (5.89%). Meanwhile themetaphorical realization of Declarative are 7 utterances (1.24%), Interrogative are2 utterances (0.36%) and Imperative only 1 utterance (0.18%). Statement as themost dominant type of speech function in this debate shows thatJokowi andPrabowoare mostly giving information in order to deliver their future plans andideas in the form of proposition, promise and persuasion, to strengthen thearguments and to convey messages logically in a limited time, so that the hearer/people of Indonesia interested in choosing him as the next President. And the useof congruent or metaphorical realization in this debate implies that both Jokowiand Prabowo are able to give and to response arguments logically in differentways.